1993
DOI: 10.1121/1.407353
|View full text |Cite
|
Sign up to set email alerts
|

A computational model of echo processing and acoustic imaging in frequency- modulated echolocating bats: The spectrogram correlation and transformation receiver

Abstract: The spectrogram correlation and transformation (SCAT) model of the sonar receiver in the big brown bat (Eptesicus fuscus) consists of a cochlear component for encoding the bat's frequency modulated (FM) sonar transmissions and multiple FM echoes in a spectrogram format, followed by two parallel pathways for processing temporal and spectral information in sonar echoes to reconstruct the absolute range and fine range structure of multiple targets from echo spectrograms. The outputs of computations taking place a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 0 publications
2
127
0
Order By: Relevance
“…It was therefore suggested that bats perceive two front echoes in the spectral domain and then translate the spectral notch pattern into a full time domain representation of the actual range profile (Simmons et al, 1990). The spectrogram correlation and transformation (SCAT) model (Saillant et al, 1993) explains the transformation of spectral information into time information. Assuming this mechanism, gap 1-2 duration may well have played a decisive role for the discrimination of different sized hollow hemispheres.…”
Section: Temporal Pattern and Spectral Domainmentioning
confidence: 99%
“…It was therefore suggested that bats perceive two front echoes in the spectral domain and then translate the spectral notch pattern into a full time domain representation of the actual range profile (Simmons et al, 1990). The spectrogram correlation and transformation (SCAT) model (Saillant et al, 1993) explains the transformation of spectral information into time information. Assuming this mechanism, gap 1-2 duration may well have played a decisive role for the discrimination of different sized hollow hemispheres.…”
Section: Temporal Pattern and Spectral Domainmentioning
confidence: 99%
“…A useful analysis of the acoustic scenes, as they are represented in sequences of echoes, requires the identification of the acoustically complex objects surrounding the animals in their natural habitat. Many studies have provided insights into the extraordinary capabilities of echolocating animals in object recognition and classification (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…We found that a receiver model incorporating the two most salient physiological features of the auditory time͞frequency representation (V-shaped tuning curves with different high-and low-frequency slopes, and an active process for compressive gain nonlinearity) replicates the relations between the bat's delay thresholds, echo bandwidth, and Q. Bats perform exceptionally well in tasks requiring classification of targets by shape by using a small number of echoes (34), and it is possible to transform time͞frequency information to depict target shape from delays (35)(36)(37)(38). Knowing that the underlying reciprocal relation is to relative bandwidth, Q, not absolute bandwidth, B, gives new insights into the nature of this transformation.…”
Section: Discussionmentioning
confidence: 99%